Theoretical and Experimental Investigation on Characters of Mechanical Pumped Two Phase Cooling System - Liu Jie; Pei nianqiang; Guo Kaihua; He Zhenhui; Li Tingxuen; Gu Jianming (Zhileng xuebao)
A brief review of two-phase cooling applications was presented.The differences between MPLHP(Mechanical Pumped Loop Heat Pipe) and LHP/CPL(Loop Heat Pipe /Capillary Pumped Loop)or Mechanical Pumped Single-phase Cooling Loop were discussed according to working mechanism and heat transfer characters.The characters of MPLHP system using CO2 as a working fluid were investigated theoretically and experimentally.The results show that the loop heat pipe driven by a mechanical pump has obvious advantages,such as lower power consumption,higher control accuracy,and compactness.